2016
DOI: 10.5811/westjem.2016.6.30233
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Lactate Measurement by Emergency Medical Services in Patients Meeting Sepsis Criteria

Abstract: IntroductionWe aimed to pilot test the delivery of sepsis education to emergency medical services (EMS) providers and the feasibility of equipping them with temporal artery thermometers (TATs) and handheld lactate meters to aid in the prehospital recognition of sepsis.MethodsThis study used a convenience sample of prehospital patients meeting established criteria for sepsis. Paramedics received education on systemic inflammatory response syndrome (SIRS) criteria, were trained in the use of TATs and hand-held l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…In order to study pLA triggers or cut‐off points we used already described thresholds 10,11 . The accuracy of pLA triggers presented relevant results which are consistent with previous studies 7,14,23 . For instance, values above 4 mmol/L, which represents a state of hyperlactatemia, 24,25 showed a significant increase in mortality.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In order to study pLA triggers or cut‐off points we used already described thresholds 10,11 . The accuracy of pLA triggers presented relevant results which are consistent with previous studies 7,14,23 . For instance, values above 4 mmol/L, which represents a state of hyperlactatemia, 24,25 showed a significant increase in mortality.…”
Section: Discussionsupporting
confidence: 74%
“…Our outcome is more restrictive than other similar studies with higher early mortality data, but with a longer temporal window, that is more than two days. 7,14,21,22 F I G U R E 1 Flow chart showing analysis population. 1 On-site resolution: either the ALS physician has been able to stabilize the patient on the scene and his/her condition was no longer serious or once the patient has been evaluated it was found that he/she does not needed any type of manoeuvre or be transferred to the ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactate is not measured by ambulance crews in the participating ambulance service, therefore it was not available for consideration during SEPSIS score development. However, it has been reported that inclusion of prehospital lactate does not improve prehospital identification of sepsis [62]. Secondly, Hunter et al argued that end-tidal carbon dioxide (EtCO 2 ) measured by EMS was an important predictor of sepsis, severe sepsis and mortality, reporting an AUROC of 0.99 (95%CI 0.99–1.0), 0.80 (95%CI 0.73–0.86) and 0.70 (95%CI 0.57–0.83) respectively [63].…”
Section: Discussionmentioning
confidence: 99%